Risk Factors for Supraspinatus Tears: A Meta-analysis of Observational Studies. Issue 10 (5th October 2021) - Zhao, Jinlong; Luo, Minghui; Liang, Guihong; Wu, Ming; Pan, Jianke; Zeng, Ling-feng; Yang, Weiyi; Liu, Jun
Background: The pathogenesis of rotator cuff tears remains unclear, and there is a lack of high-quality evidence-based research on the risk factors for supraspinatus tears. Purpose: To explore 10 potential risk factors for supraspinatus muscle tears. Study Design: Systematic review; Level of evidence, 3. Methods: This review was conducted according to the MOOSE (Meta-analysis Of Observational Studies in Epidemiology) guidelines. PubMed, Embase, and Web of Science were searched for cohort, case-control and cross-sectional studies published before January 2021 on supraspinatus tears. The following potential risk factors were analyzed: age, body mass index, male sex, female sex, arm dominance, diabetes mellitus, smoking, hypertension, thyroid disease, and the critical shoulder angle (CSA). Risk ratios (RRs) or weighted mean differences (WMDs) of related risk were calculated. The Egger test was used to evaluate publication bias. Results: A total of 9 articles from 8 countries were included; among the 3240 patients, 687 were included in the supraspinatus tear group, and 2553 were included in the nonsupraspinatus tear group. The meta-analysis showed that older age (WMD, 3.36 [95% confidence interval (CI), 0.53-6.20]; P = .02), male sex (RR, 0.87 [95% CI, 0.78-0.97]; P = .01), smoking (RR, 2.21 [95% CI, 1.56-3.14]; P < .00001), diabetes (RR, 1.67 [95% CI, 1.03-2.70]; P = .04), hypertension (RR, 1.51 [95% CI, 1.16-1.97]; P = .002), and the CSA (WMD, 2.25 [95% CI, 1.39-3.12]; P < .00001) were risk factors for supraspinatus tears. Conclusion: Older age, male sex, smoking, diabetes, hypertension, and a higher CSA were found to be risk factors for supraspinatus tears in this meta-analysis review. Identifying risk factors for supraspinatus tears early can help clinicians identify these high-risk patients and choose appropriate treatments.